2011
DOI: 10.1007/s11832-011-0358-y
|View full text |Cite
|
Sign up to set email alerts
|

Exposed versus buried wires for fixation of lateral humeral condyle fractures in children: A comparison of safety and efficacy

Abstract: Introduction Displaced fractures of the lateral condyle of the humerus are usually treated with open reduction and fixation with smooth Kirschner wires. These may be passed through the skin and left exposed or buried subcutaneously. Exposed wires may be removed in the outpatient clinic, whereas buried wires require a formal procedure under anaesthesia. This advantage may be offset if there is a higher rate of complications with exposed wires. The aim of this study was to compare the safety and efficacy of expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 15 publications
3
47
2
Order By: Relevance
“…A paper by Chan and Siow [13] studied 75 patients and concluded that there was no significant difference in complications with buried versus unburied wires.…”
Section: Discussionmentioning
confidence: 99%
“…A paper by Chan and Siow [13] studied 75 patients and concluded that there was no significant difference in complications with buried versus unburied wires.…”
Section: Discussionmentioning
confidence: 99%
“…Chan and Siow compared the 2 treatment options in a retrospective cohort analysis of 42 buried wires versus 33 exposed wires 8 . There was a low complication rate with one superficial infection and two cases of overgranulation, all in the exposed wires group.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is likely that unburied wires might be more prone to pin site infection and a after deep infection. [ 7 ] The duration of unburied fixation for reducing the probability of infection is about 4 weeks; however, a short duration of unburied fixation may provide inadequate time for secure union. [ 15 , 16 ] Conversely, buried K-wires can be left in place until surgeons have explicit radiographic evidence of fracture union.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies comparing the outcome between buried and unburied K-wires have been published in past years. [ 7 , 16 18 ] However, there is no clear consensus as to whether K-wires should be buried or left unburied outside the skin. Consequently, we performed a meta-analysis concerning buried or unburied internal fixation treatment of lateral condyle distal humeral fractures in children to provide evidence for making a clinical decision.…”
Section: Introductionmentioning
confidence: 99%